Peripheral Retinal Changes Associated with Age-Related Macular Degeneration in the Age-Related Eye Disease Study 2: Age-Related Eye Disease Study 2 Report Number 12 by the Age-Related Eye Disease Study 2 Optos PEripheral RetinA (OPERA) Study Research Group - Domalpally, Amitha; Clemons, Traci E; Danis, Ronald P; Sadda, SriniVas R; Cukras, Catherine A; Toth, Cynthia A; Friberg, Thomas R; Chew, Emily Y (Ophthalmology (Rochester, Minn.), 2017)
To compare rates of peripheral retinal changes in Age-Related Eye Disease Study 2 (AREDS2) participants with at least intermediate age-related macular degeneration (AMD) with control subjects without intermediate age-related changes (large drusen). Cross-sectional evaluation of clinic-based patients enrolled in AREDS2 and a prospective study. Participants from prospective studies. The 200° pseudocolor and fundus autofluorescence (FAF) images were captured on the Optos 200 Tx Ultrawide-field device (Optos, Dunfermline, Scotland) by centering on the fovea and then steering superiorly and inferiorly. The montaged images were graded at a reading center with the images divided into 3 zones (zone 1 [posterior pole], zone 2 [midperiphery], and zone 3 [far periphery]) to document the presence of peripheral lesions. Peripheral retinal lesions: drusen, hypopigmentary/hyperpigmentary changes, reticular pseudodrusen, senile reticular pigmentary changes, cobblestone degeneration, and FAF abnormalities. A total of 484 (951 eyes) AREDS2 participants with AMD (cases) and 89 (163 eyes) controls without AMD had gradable color and FAF images. In zones 2 and 3, neovascularization and geographic atrophy (GA) were present, ranging from 0.4% to 6% in eyes of cases, respectively, and GA was present in 1% of eyes of controls. Drusen were detected in 97%, 78%, and 64% of eyes of cases and 48%, 21%, and 9% of eyes of controls in zones 2 and 3 superior and 3 inferior, respectively (P < 0.001 for all). Peripheral reticular pseudodrusen were seen in 15%. Senile reticular pigmentary change was the predominant peripheral change seen in 48% of cases and 16% of controls in zone 2 (P < 0.001). Nonreticular pigment changes were less frequent in the periphery than in the posterior pole (46% vs. 76%) and negligible in controls. Peripheral retinal changes are more prevalent in eyes with AMD than in control eyes. Drusen are seen in a majority of eyes with AMD in both the mid and far periphery, whereas pigment changes and features of advanced AMD are less frequent. Age-related macular degeneration may be more than a "macular" condition but one that involves the entire retina. Future longitudinal studies of peripheral changes in AMD and their impact on visual function may contribute to understanding AMD pathogenesis.